MOTIF DAN KEPUASAN ANAK MUDA KOTA DENPASAR DALAM PENGGUNAAN FITUR REELS PADA MEDIA SOSIAL INSTAGRAM - Georgenia, Maria Priscillia; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2022)
The Reels feature is the latest innovation from the Instagram application. The Reels feature on the Instagram application has been released in Indonesia since June 23, 2021. This feature allows users to create short videos with a maximum duration of 60 seconds with a choice of audio, effects, and other creative tools. This study aims to determine the motives and satisfaction of young people in Denpasar in using the Reels feature on the Instagram application. The subjects of this study were young people from Denpasar City with an age range of 16-30 years old. The city of Denpasar was chosen as the research location because it was recorded as the city that has the highest number of internet users in the province of Bali. This study uses the motives of Dennis McQuail, namely information motives, personal identity motives, integration motives and social interaction and entertainment motives. The theory used in this research is Uses and Gratifications Theory. This research using descriptive quantitative methods with sampling techniques purposive sampling. Data collection is obtained by distributing a questionnaire that uses a Likert scale. The results of this study indicate that the four motives are satisfied, namely the information motive, the personal identity motive, the integration and social interaction motive, and the entertainment motive. Based on the results of this study, the motive that most motivated respondents to use the Reels feature was the information motive. Keywords : Youth, Denpasar, Instagram Reels, Satisfaction, Motive